2015
DOI: 10.1016/j.euromechsol.2015.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Rolling induced size effects in elastic–viscoplastic sheet metals

Abstract: Rolling processes for which the characteristic length scale reaches into the range where size effects become important are receiving increased interest. In particularly, this is owed to the roll-molding process under development for high-throughput of micronscale surface features. The study presented revolves around the rolling induced effect of visco-plasticity (ranging hot and cold rolling) in combination with strain gradient hardening -including both dissipative and energetic contributions. To bring out fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 24 publications
2
4
0
Order By: Relevance
“…The presented results and observations establish the findings reported in , and Nielsen (2015) as a widespread phenomenon, and show that by exploiting it, results at the rate-independent limit may, in fact, be reached for the present model, which only exists in a rate-dependent framework. It should be made clear, however, that the phenomenon is a purely theoretical concept and, to the best of the authors knowledge, remains to be observed in experiments.…”
Section: Resultssupporting
confidence: 68%
See 1 more Smart Citation
“…The presented results and observations establish the findings reported in , and Nielsen (2015) as a widespread phenomenon, and show that by exploiting it, results at the rate-independent limit may, in fact, be reached for the present model, which only exists in a rate-dependent framework. It should be made clear, however, that the phenomenon is a purely theoretical concept and, to the best of the authors knowledge, remains to be observed in experiments.…”
Section: Resultssupporting
confidence: 68%
“…The idea of a characteristic rate was first discussed in detail by in relation to conventional rate-dependent steady-state modeling and later exploited in to extract rate-independent results from a scale-dependent steady-state framework. Nielsen (2015) also found similar results for steady-state sheet rolling. Characteristic rates may exist for a wide range of other structural problems, and a broader sense of the phenomenon is demonstrated through the results of the present study.…”
Section: Introductionsupporting
confidence: 73%
“…the rolling process is essentially modeled rate-independent (for a rate-dependent study see e.g. [30]).…”
Section: Problem Formulationmentioning
confidence: 99%
“…In case of friction, an additional traction parallel to the movement should be added to contact interface depending on the direction of sliding relative to the tool. For details relating to the implementation of friction in the context of steady-state solutions please refer to (Nielsen et al, 2016;Nielsen, 2015).…”
Section: Contact Modellingmentioning
confidence: 99%